Segmented Re/integration: Divergent Post-Deportation Trajectories in El Salvador. (15th March 2017) - Dingeman, Katie
Abstract: This study extends segmented assimilation to post-deportation studies. Drawing from life history interviews with 96 deported Salvadoran men, it argues that deportees follow different paths to re/integration upon return. Divergent trajectories are explained by an interaction between the context of return (government policies, social reception, economic structure, and the deportee community), migrant characteristics (demographics, criminal and migratory histories, economic resources, and social ties), and agentic behavior. In El Salvador, national affiliations and perceptions of deportee criminality emerge as the best predictors of post-deportation outcomes. Deportees who grew up in El Salvador and remained connected to it while abroad ( Salvadoran Nationals ) encountered a relatively more favorable societal reception but faced a precarious economic situation. Conversely, deportees who spent significant time in the U.S. and continued identified with it prior to removal ( U.S. Nationals ) were highly stigmatized and criminalized upon return. U.S. nationals struggled to find employment and were targeted by police and gangs. Regardless of sociocultural and economic outcomes, both Salvadoran nationals and U.S. nationals longed to return to the U.S., especially if they had children abroad. The study affirms existing research claiming that mass deportation may slow but does not stop the migration cycle in the Americas. It also offers an analytical framework for future comparative post-deportation research.